A polarization‐insensitive frequency selective rasorber with wideband high‐transmission passband and absorption. Issue 12 (14th October 2022) - Yang, Yukun; Liu, Shaobin; Liao, Kun; Wang, Lingling
Abstract: A polarization‐insensitive frequency‐selective rasorber (FSR) with a high‐transmission passband and two wide absorption bands is proposed. The proposed FSR consists of an absorptive layer and a frequency selective surface (FSS) layer. The absorptive layer employs a four‐arm square spiral resonator with four fork shape resonators connected by lumped resistances to form broadband transmission and absorption. The FSS layer is formed by three metallic patches and two dielectric substrates, which are applied to generate a wide passband. The simulated results demonstrate that the 1‐dB transmission passband enables to obtain of 40.2% fractional bandwidth (FBW) from 9 GHz to 13.53 GHz, and the minimum in‐band insertion loss (IL) is 0.07 dB. Besides, the reflection bandwidth below −10 dB can reach 135% from 3.29 GHz to 16.90 GHz. Finally, the FSR's prototype is fabricated and measured. The results of measurement are fitted well with the simulated ones, which means that the proposed FSS can achieve broadband transmission and absorption.